On the diverse bonding situations in nanostructures : an ab initio computational study - Pankewitz, Tobias (KIT Scientific Publishing, 2010)
This computational study investigates diverse bonding situations in nanostructures (carbon nanotubes, fullerenes, metal compounds) spanning a broad range of energies. Weak, dispersive interactions and covalent metal-ligand and metal-metal bonding are examined. The results of efficient density functional calculations are compared to those of correlated wavefunction calculations on model systems. This rigorous validation is crucial in evaluating the balance between computational cost and accuracy.